De quelques aspects de la réassurance - Parizeau, Robert (Assurances, 1982)
After reviewing the present state of the market, the author concludes as follows: “Whether we like it or not, Canada is affected by developments in the London and American markets, and will certainly be influenced by these structural changes, as regards both insurance and reinsurance. In the long run, the major insurers in Canada will have to seek new outlets in order to keep their share of the market. If Canadian insurers do not do so, foreign companies will do it for them. The recent acquisition of the Belair by the Commerce Groupe is very significant in this respect. Indeed, this situation has been a major factor in the development of the Sodarcan group over the past few years.”